Household Activities and Greenhouse Gas Emissions Value: Lessons from a Neglasari Household Survey - Afiana, Riyyun; Hidayat, Aceng; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal (Business and Sustainability, 2024)
The escalating threat of global warming stems from greenhouse gas emissions resulting from various household activities, profoundly impacting climate change. This study delves into Neglasari Village, Bogor Regency, scrutinizing emissions' correlation with household consumption. Predominantly focusing on carbon dioxide, methane, and nitrous oxide, emissions arise from electricity, cooking and oil fuel usage, waste, agriculture, and livestock farming. Objectives encompass elucidating and computing greenhouse gas emissions, discerning influential factors, and gauging their economic ramifications. Employing IPCC's 2006 emission valuation, multiple linear regression, descriptive analysis, and carbon economic metrics, findings reveal Neglasari Village's emissions total 1,247,364.80 kg CO₂-e/month, averaging 411.40 kg CO₂-e/month per household. Key influencers identified are household income and house ownership status. The calculated carbon economic value stands at IDR138,646/month per household, aggregating to IDR421,809,752/month across Neglasari Village, fortifying the imperative for sustainable practices.